Types of linguistic units related to public catering and their specific characteristics - Sherboyev , Nosir Anorboyevich (The Lingua Spectrum, 2026)
Language, as the most important socio-cultural phenomenon of humanity, functions in all spheres of social life. In this regard, the field of public catering is also one of the areas in which language has a direct impact and represents a distinct linguocultural layer. This is because the names of dishes, products, methods of food preparation, kitchen utensils, ritual foods, and lexical units related to consumption culture have developed as linguistic signs that reflect a people’s national culture, ethnic traditions, and social values. Language serves as the primary means of communication in all areas of human activity, particularly in socio-cultural and economic life. The field of public catering, in turn, is one of the most active spheres of human activity from communicative, social, and cultural perspectives, and the lexical units used in this sphere (restaurant, café, menu, order, service, chef, customer, waiter, etc.) form a specific linguistic system. They are interpreted not only as means of describing the process of eating, but also as a system of cultural signs that express social interaction, service culture, and national norms of etiquette.